International money and finance - Makin, A. J. (Routledge, Taylor & Francis Group, 2017)
"This textbook focuses on key international monetary and financial phenomena, exploring the determinants of exchange rates, international competitiveness, interest rates, saving, investment, international capital flows, commodity prices, the terms of trade, financial crises, foreign investment and economic growth. The text enhances understanding of international money and finance by providing background on globalisation and characteristics of the world economy, as well as detailed explanation of important international monetary variables. It then systematically develops a suite of compatible theoretical frameworks to analyse perennially important international monetary questions."--Provided by publisher.